Effect of operating parameters on the effectiveness of electric field enhanced separations - Jami, Mohammed Saedi; Iwata, Masashi (Taylor & Francis, 2008)
The purpose of this work is to summarize our latest research results about constant-current electroosmotic dewatering (EOD). The Terzaghi-Voigt combined model is used for the analysis of EOD of various solid-liquid systems by considering the creep deformation of the material. Bentonite clay, KC-flock, zinc oxide, and some of their mixtures are used as experimental materials. It is assumed that the electroosmotic pressure gradient Epg and modified consolidation coefficient Ce of the materials are constant. The relation between the ratio of creep deformation to total deformation B and the modified consolidation coefficient Ce is determined and compared with previous observations for the case of mechanical expression. The effectiveness of dewatering is described depending on operating parameters such as preconsolidation pressure, material composition, electric current density, and total solid volume per unit cross-sectional area. The model is verified by comparing the calculations with experimental data.